Forest health: context of forest pests and pathogen in Nepal - Pokharel, Kiran Kumar (Banko Janakari, 2018)
Not available. Banko Janakari A Journal of Forestry Information for Nepal Vol. 27, No. 2, 2017, Page: 1-2